“That Place Where the Wave Finally Broke and Rolled Back”: Modernism and Adolescent Psychological Development - Gage, Alex (Revue YOUR Review (York Online Undergraduate Research), 2017)
Modernism represents the crisis of opportunity: a period of liminality brought about by intense and sustained changes in technology and society is accompanied by an unbalancing expansion of possibilities for the individual in this new and mutable landscape. Understanding this unprecedentedly unpredictable world required contemporaries of the modern era to develop a correspondingly “modern” consciousness. We can deepen our understanding of this process by drawing analogies to adolescent psychological development—a period in the individual’s life that serves as a more-than-apt analogue for exploring the historical period of Modernism. Using the archetype of “modern man” as observed and represented by German author Johann Wolfgang von Goethe in his metaphorically sensitive parable, Faust, as a launching point, it is possible to identify corollary developments in the history of Modernism and the modern subject and adolescent psychological development.